Intervención Educativa, Intervención Pedagógica y Educación: La Mirada Pedagógica - Touriñán López, José Manuel (Revista Portuguesa de Pedagogia, 2011)
Education is an activity and a field of reality which becomes a study or analysis matter in a general, vocational and professional sense. Several scientific disciplines and, in an outstanding way, Pedagogy, contribute to the knowledge of education. The knowledge of education differs from the knowledge of cultural areas and it uses the cultural areas to educate. Each cultural area has to be valued as education and built as education field from Pedagogy. The pedagogical look (approach) provides arguments to not confuse “to know a cultural area”, “to teach a cultural area” and “to educate with a cultural area”. This article addresses the uniqueness of the knowledge of education and its connection to the knowledge of cultural areas, regarding the meaning of education and the concept of education field.